"If I had a regular bicycle, I wouldn't be out riding anymore": Perspectives on the potential of e-bikes to support active living and independent mobility among older adults in Waterloo, Canada. (May 2019) - Leger, Samantha J.; Dean, Jennifer L.; Edge, Sara; Casello, Jeffrey M.
Abstract: The predominance of automobile dependency in North America is associated with a host of negative health and environmental impacts and has sparked the promotion of low-carbon and active modes of transportation. Encompassing both priorities, electric-bicycles have become a popular mode of transportation in some parts of the world. While multiple studies have suggested older adult populations may be most likely to benefit from e-bike technology, few studies have exclusively focused on this demographic to identify the factors that may promote or inhibit e-bike adoption amongst this group. This study explores the potential for e-bikes to support independent mobility and active aging among the older adult population in Canada's auto-dependent context. Guided by a conceptual framework for older adult mobility, this study used qualitative methods to gather perceptual and experiential data from 17 community stakeholders and 37 older adults in the Region of Waterloo, Ontario. The findings highlight the importance of cycling life histories, social connection and physical limitations to adopting cycling later in life. Specific individual and structural factors were discussed in relation to e-bike adoption including facilitators such as increased convenience, reduced physical exertion, reduced reliance on a vehicle and fun. Barriers included cycling infrastructure and road safety, regulation, and stigmatization barriers. E-bikes as a more convenient and supportive mode of transit for older adults is discussed alongside the importance of e-bikes as a replacement for traditional bicycles in a subset of this population.